Knowledge of Postpartum Mother And Husband’s Support Regarding Postpartum Birth Control In Tembuku II - Ni Ketut Siarni; Made Widhi Gunapria Darmapatni; Ni Made Purnamayanthi (Gaster, 2025)
Background: The Postpartum Birth Control/Family Planning Method is an effort to prevent pregnancy by using contraceptive devices and drugs immediately after giving birth up to 42 days/6 weeks after giving birth. The achievement of Postpartum Birth Control/Family Planning in Tembuku II Public Health Center in 2023 was 17.54%, it's still under the target. Purpose:This study aims to determine the knowledge of postpartum mothers and husbands' support regarding the use of postpartum Birth Control/Family Planning in Tembuku II Public Health Center, Bangli Regency. Method: This type of research is quantitative descriptive using a crosssectional approach. The study was conducted from March to May 2024 with a sample of 56 postpartum mothers. Data collection and retrieval was using a questionnaire with a Likert scale. Result:The results of the study found that 22 people (39.28%) had propper knowledge, 30 people (53.58%) had sufficient knowledge, and 4 people (7.14%) had insufficient knowledge. Meanwhile, husbands' support was found to be good support of 31 people (55.35%), and husbands' support was sufficient of 25 people (44.65%). Conclusion:The conclusion of the study found that most of mothers had sufficient knowkedge and supported by their husbands. In improving postpartum birth control/family planning achievement, it is necessary to pay more attention to the mother's knowledge and husband's support.